Impacts of volcanic ejecta on surface water Mt. Pinatubo case - Villados, Danilo P.
This study was designed to determine the possible effects of volcanic materials on the surface water of Pampanga River following the deposition of sediments particularly during the rainy season. After the June 1991 eruptions of Mt. Pinatubo, tons of volcanic debris had been deposited over a broad area. On the onset of the rainy season, t hese volcanic materials and pyroclastic fall deposits are mobilized, blocking up all available spaces towards low-lying area. Lahar, a mixture of water and volcanic debris from Mt. Pinatubo contains sediments and minerals which may contaminate rivers along the periphery of Mt. Pinatubo and low-lying rivers including the Pampanga River. The Pampanga River is one of the most important rivers in Cental Luzon suppying about 14,716 million cubic meters of water for agricultural, industrial and domestic/municipal use. At present, the surface water of Pampanga River is being used largely for irrigation of various crops.